2021
DOI: 10.18844/cjes.v16i5.6344
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Pre-service teachers’ intention to implement education for sustainable development: A fuzzy-set qualitative comparative analysis

Abstract: Implementation of Education for Sustainable Development is a complex social phenomenon. This research aims to suggest ways to strengthen the implementation of ESD, identifying the factors affecting pre-service teachers’ intention of implementing ESD. To this end, the author focused on revealing the different combinations of conditions predicting Korean pre-service teachers’ intention to implementing education for sustainable development (ESD). The research method is the fuzzy sets qualitative comparative analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
(36 reference statements)
1
3
0
Order By: Relevance
“…Based on the results of these observations and interviews, it was concluded that it was necessary to develop an e-module ESD to improve students' creative thinking skills and sustainable awareness of the theme of traditional Indonesian fermented foods. This is in line with research conducted by Kang (2021), Ang (2021), andAmmoneit et al, (2022) that teacher need to include content related to ESD in the teacher education curriculum so that teachers can cultivate positive attitudes toward ESD and improve their self-efficacy in student engagement and instruction in the context of ESD. Educators have a pivotal role in promoting education for sustainable development (ESD).…”
Section: ▪ Results and Disscussionsupporting
confidence: 83%
“…Based on the results of these observations and interviews, it was concluded that it was necessary to develop an e-module ESD to improve students' creative thinking skills and sustainable awareness of the theme of traditional Indonesian fermented foods. This is in line with research conducted by Kang (2021), Ang (2021), andAmmoneit et al, (2022) that teacher need to include content related to ESD in the teacher education curriculum so that teachers can cultivate positive attitudes toward ESD and improve their self-efficacy in student engagement and instruction in the context of ESD. Educators have a pivotal role in promoting education for sustainable development (ESD).…”
Section: ▪ Results and Disscussionsupporting
confidence: 83%
“…Understanding the field of study will aid in identifying the ESD teacher education gap and main focus. A large percentage of ESD research in teacher education has been accomplished with the participation of pre-service teachers in a mixture of field studies which is 31% of the whole articles included; (Gopalakrishnan et al, 2019;Kang, 2019;Manasia et al, 2020;Avsec & Ferk Savec, 2021;Echegoyen-Sanz & Martín-Ezpeleta, 2021;Kalsoom & Qureshi, 2021;Kang, 2021, Nousheen & Kalsoom, 2022. This demonstrates that the ESD integration does not have any boundaries between fields.…”
Section: Ro1: Common Fields Of Studies Involved In Preparing Pre-serv...mentioning
confidence: 98%
“…Author & Year Sustainability Consciousness (Kalsoom et al, 2017), (Colas-Bravo et al, 2018, (Nousheen & Kalsoom, 2022) Views/understanding/beliefs of ESD (Andersson, 2017), (Bezeljak et al, 2020), (Ateş & Gul, 2018) Sustainability awareness/attitudes/actions (Sunthonkanokpong & Murphy, 2019), (Nousheen et al, 2020), (Echegoyen-Sanz & Martín-Ezpeleta, 2021) Personal pedagogical knowledge/teachers' agency/professional competencies (Gopalakrishnan et al, 2019), (Kalsoom & Qureshi, 2021), (Ammoneit et al, 2022) thinking skill (Strakova & Cimermanova, 2018), (Semiz & Teksoz, 2020) Experiences with technology-enhanced transformative learning/experiences of project based learning (Avsec & Ferk Savec, 2021), (Singh-Pillay, 2020) Self-efficacy (Malandrakis et al, 2019) Teaching readiness (Manasia et al, 2020) Intention to implement ESD (Kang, 2021) Other: Gender, the students' habitual place of residence, the type of leisure activities, educational factors, barrier, social media usage, subject discipline (Alvarez-Garcia et al, 2019), (Kang, 2019), (Gopalakrishnan et al, 2019) To aid discussion, variables may be split into three categories: pre-ESD experience, post-ESD experience, and external factors.…”
Section: Variablesmentioning
confidence: 99%
See 1 more Smart Citation